A conceptual model to manage lexical ambiguity in Malay textual requirements - Haron, Hazlina; Abd Ghani, Abdul Azim; Haron, Hazliza (Asian Research Publishing Network, 2015)
Ambiguity is one of the most crucial problem in natural language. When a sentence can be interpreted in more than one ways by different sets of readers, the impact is huge. It would involve many stages in system development life cycle from requirement elicitation to requirement transformation, system design, system coding as well as the end product. It is very important to ensure requirement requested by the users accurately transformed onto the end system as per desired. More often than not, the understanding between users and system developer is not tele. In this paper, we attempt to publish a conceptual model on managing lexical ambiguity to reduce the possibility of misinterpretation errors in Malay sentences. The approach that we used is by identifying potential Malay vague words based on vague criteria and mapped onto constructed Requirement Ambiguity Attributes (RAA). We designed a Model of Vagueness that has the elements of vague criteria that is mapped with RAA as a hybrid method to detect potential ambiguous sentences.